Analisis Kinerja BAPENDA Dalam Meningkatkan Penerimaan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (PBB-P2) Di Kabupaten Tangerang Tahun 2021–2023 - Fiatri, Lisa Arisa; Wijaya, Annisa Rifka (CV ODIS, 2025)
This study analyzes the performance of the Tangerang Regency Regional Revenue Agency (BAPENDA) in increasing the revenue of Rural and Urban Land and Building Tax (PBB-P2) during the period 2021-2023. This study used a descriptive qualitative approach and Mahsun's (2020) organizational performance theoretical framework that includes inputs, processes, outputs, outcomes, and impacts. This study aims to evaluate the effectiveness of the strategy, identify obstacles, and formulate improvement efforts. The results showed that BAPENDA Tangerang Regency's performance in PBB-P2 revenue is relatively good, with stable realization and close to the target (98.40% in 2021, 95.51% in 2022, and 100% in 2023). Nevertheless, several problems were found. Internal constraints include the limited number and competence of field human resources, as well as suboptimal data integration between agencies. External constraints include low literacy and community participation in data collection, and the impact of economic conditions that affect taxpayer compliance. To overcome these problems, BAPENDA needs to keep making innovations such as increasing the capacity of human resources through training, optimizing service digitization (e-SPPT, online payment), and more intensive and interactive socialization by involving local communities. Transparency in the use of tax funds is also crucial to build public trust and improve compliance. This study recommends improvements to the data system, active community involvement in data collection, and more effective communication about the benefits of taxes for the optimization of PBB-P2 revenue and sustainable regional fiscal independence.